The procedure of filing the motion (vote) of no confidence as one of the forms of parliamentary responsibility of the Cabinet of Ministers of Ukraine - Lykhachov, Nikita (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
This article is conducting a research on parliamentary responsibility of the Cabinet of Ministers of Ukraine – the motion (vote) of no confidence, in particular, as one of its forms. The notion and attributes of parliamentary responsibility of the Ukrainian government are revealed and analysed in the article. In addition, the procedure of filing the motion of no confidence is considered